Perlindungan terhadap Pekerja Disabilitas Akibat Kecelakaan Kerja : (Studi Kasus PT Xyz) - Annisa Olivia Restiani; Mudiana Permata Sari; Yeski Putri Utami (POLITEKNIK KETENAGAKERJAAN, 2025)
Every company always prioritizes Occupational Safety and Health (OSH), yet workplace accidents that result in permanent disability may still occur. In such cases, workers should not be immediately terminated from employment due to physical impairments caused by work-related accidents. This study uses a qualitative approach with a case study method. The results indicate that PT XYZ has demonstrated a commitment to providing protection by not conducting employment termination and instead adjusting job placements (redeployment) for workers who become disabled. However, the company has yet to provide specific training or facilities for disabled workers. Existing laws and regulations such as the 1945 Constitution, Law Number 13 of 2003 concerning Manpower, and other relevant legal instruments are comprehensive in regulating the protection of the rights of workers with disabilities. Nevertheless, their implementation has not been fully realized by all companies.